Fraud Prevention in the Village Fund System: A Case Study in Marga Mulya Village, Tangerang - Septian Bayu Kristanto (Asia Pacific Fraud Journal, 2023)
The purpose of this study is to examine fraud prevention in the village fund system using the metrics stated in Permendesa No.19 of 2020. SISKEUDES were formed by the Financial and Development Supervisory Agency (BPKP) to enhance village government and financial management. Internal control is an important component in mitigating the possibility of village money being misused. The qualitative descriptive approach was used to conduct the research at Marga Mulya Village. Data was collected through interviews and observations, and data triangulation was employed as an analytical tool. Internal control in the village financial system has been implemented fairly effectively, according to the study’s results and discussion, as internal control efforts have been applied to each indicator in Permendesa No.19 of 2020. However, there is still a risk of fraud because various internal control indications that have been created have not been followed up on in a timely and appropriate manner